2020
DOI: 10.3390/antibiotics9060306
|View full text |Cite
|
Sign up to set email alerts
|

HNP-1 and HBD-1 as Biomarkers for the Immune Systems of Elite Basketball Athletes

Abstract: Acute or strenuous exercise is sometimes related to upper respiratory tract infections in athletes. Practicing intense and regular exercise can lead to incorrect activation of the immune system, causing athletes to be excluded from training programs and competitions. Defensins are small antimicrobial peptides that are part of the innate immune system and dynamically involved in several biological activities. In this study, we highlight the role of human defensins in competitive basketball athletes. In particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 69 publications
(99 reference statements)
0
26
0
Order By: Relevance
“…The beneficial effects of exercise are well known [35]. It has been widely demonstrated that physical exercise can prevent infections [36][37][38], inflammation and delay the onset of cardiovascular and muscular pathologies [39,40]. In this scenario, the practice of physical activity conducted according to the ANTI-COVID-19 rules, and a correct diet, such as Mediterranean Diet can represent a valid tool to combat weight gain and depressive moods that can characterize periods such as those of quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of exercise are well known [35]. It has been widely demonstrated that physical exercise can prevent infections [36][37][38], inflammation and delay the onset of cardiovascular and muscular pathologies [39,40]. In this scenario, the practice of physical activity conducted according to the ANTI-COVID-19 rules, and a correct diet, such as Mediterranean Diet can represent a valid tool to combat weight gain and depressive moods that can characterize periods such as those of quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the effects of exercise on the immune system have been carried out [27][28][29][30] by evaluating some parameters before and after physical performance. Single bouts of moderate-intensity exercise are "immunoenhancing", and in fact, are responsible for a reduction in inflammation, maintenance of thymic mass and enhanced immunosurveillance [31].…”
Section: Effect Of Exercise On Immunity: Open Window Theorymentioning
confidence: 99%
“…However, the main source of ROS in the human body is the immune system [ 51 ], as the immune system together with its components is involved in the defense of the organism from external stimuli that can trigger the inflammatory process [ 52 , 53 , 54 ] or from internal stimuli of cell regeneration [ 55 ].…”
Section: Mechanisms Of Oxidationmentioning
confidence: 99%